Student teams achievement divisions (STAD) to enhance learning outcome - Siti Patimah; Slameto Slameto; Eunice W. Setyaningtyas (Universitas Pendidikan Ganesha, 2018)
This study aimed at determining the increase in students’ learning outcomes in social science by applying the student teams achievement divisions (STAD) model with the steps based on Curriculum 2013. This research was a type of a classroom action research which was conducted in two cycles in 33 fourth grade students in a primary school in Salatiga in second semester of academic year 2017/2018. Data was collected using test and non-test techniques with help of evaluation test and an observation sheet. Results show improvement of learning outcomes by applying STAD model on social science subjects. The average completeness of learning outcomes increased from pre-cycle to cycle II. At pre-cycle, the average was 57.71 with 31,42% completeness, at cycle I was 68.28 with 50% completeness, and cycle II was 70 with 71.87% completeness. Therefore, applying the STAD model can improve the learning outcomes of primary students in social science.